Effect of Low Lactose Milk Eiwit Melk (E.M.) on Protein Calorie Malnutrition - Suharjono Suharjono; I.G.N. Wila Wirya; Samsudin Samsudin; Sunoto Sunoto; Z. Sulaiman; Sutedjo Sutedjo (Paediatrica Indonesiana, 1975)
During 1Â½ years, from January 1972 until July 1973, 55 P.C.M. children hospitalised in the Department of Child Health, Medical School, University of Indonesia/Dr. Tjipto Mangunkusumo General Hospital, were involved to this study. Self-prepared "Eiwit Melk (E.M.)" containing protein 2.7%, carbohydrate (lactose) 1.4%, fat 2.2% and calories 600, was used. Thirty children were treated with E.M. and 25 children as controlled, i.e. treated with E.M. + lactose 3.4% (E.M.L.). The results of the clinical trial as expressed with the increase of body weight, were excellent in 85.7% and good in 14.3%, whereas the results in the controlled group were excellent in only 9.1%, good in 36.4% and poor in 54.5%. From these excellent results, low lactose milk formula might be recommended in treating children with P.C.M.